Integrated analysis of hub genes and intrinsically disordered regions in triple-negative breast cancer - Azhar Iqbal; Faisal Ali; Sulaiman Ali Alharbi; Muhammad Sajid; Saleh Alfarraj; Momina Hussain; Tehmina Siddique; Rakhshanda Mustaq; Fakhra Shafique; Muhammad Sarfaraz Iqbal (Journal of Genetic Engineering and Biotechnology)
Triple-negative breast cancer (TNBC) is the most prevalent breast cancer subtype. Its prognosis is poor because there are no effective treatment targets. Despite several attempts, the molecular pathways of TNBC remain unknown, posing a significant clinical barrier in the search for viable targets. Two microarray datasets were used to identify possible targets for TNBC, GSE38959 and GSE45827, retrieved from the Gene Expression Omnibus (GEO) database. Differentially expressed genes (DEGs) in TNBC samples compared with normal samples were identified using the GEO2R program. KEGG pathway enrichment and Gene Ontology functions were assessed for DEG pathways and functional annotation using ShinyGO 0.77. The STRING database and Cytoscape program were used for protein-protein interaction (PPI) analysis. Furthermore, we evaluated the predictive significance of hub gene expression in TNBC patients using the GEPIA2 online tool. We developed a comprehensive technique to assess whether intrinsically disordered regions (IDRs) are present in the TNBC hub genes. There were 48 DEGs were identified, all of which were upregulated. A putative protein complex containing these four core genes was selected for further analysis. Breast cancer patients with TTK, TOP2A, CENPF, and CCNA2 upregulation had a poor prognosis; TTK and CCNA2 were partially disordered, whereas TOP2A and CENPF were primarily disordered, according to IDR analysis. According to our study, TOP2A and CENPF may be useful therapeutic targets for disruption of the TNBC PPI network.